Procedural dungeon generation in RPG games. Issue 10 (4th December 2017) - David, David; Agung, Albertus; Tirana, Yudy
Abstract : Purpose: The purpose of this paper is to develop and evaluate a procedural dungeon generation application that created a variant dungeon floor. Procedural dungeon generation makes it easy for a designer to design a level. The result shows that the algorithm can create a variant dungeon based on the parameter on the game. This game also has a high re-playability, thanks to the generation process. Design/methodology/approach: Research methods include methods of data collection, design and implementation. Data collection was done through research literature, questionnaires and analyzing some similar applications. Designing game application using game design document and implementation was the done using the waterfall model and the unity game engine. Findings: Procedural dungeon generation is important when designing the game. If done correctly, it will reduce the designer's time to design the map especially in dungeon, where in the dungeon, there are many floors and each floor must be designed differently based on the difficulty level of the game. The application uses the combined algorithm to create a variant dungeon, where each algorithm has its own advantages that the designer can use to design the variety of the dungeon. It also opens more algorithms to be used when creating the dungeon. Originality/value: This paper uses the combined algorithm for procedural dungeon generation, and the result shows that a player has high re-playability to the game.